Voice & vision a creative approach to narrative film and DV production - Hurbis-Cherrier, Mick (Focal Press, 2007)
Voice & Vision is a comprehensive manual for the independent filmmakers and film students who want a solid grounding in the tools, techniques, and processes of narrative film in order to achieve their artistic vision. This book includes essential and detailed information on relevant film and digital video tools, a thorough overview of the filmmaking stages, and the aesthetic considerations for telling a visual story. The ultimate goal of this book is to help you develop your creative voice while acquiring the solid practical skills and confidence to use it. Unlik.
Includes bibliographical references (pages 525-527) and index. - Includes filmography: pages 509-523. - Print version record
Keywords: Motion pictures -- Production and direction; Digital video; Digitaler Film; Produktion; Lehrmittel; Cinéma; Production et réalisation; Vidéo numérique; PERFORMING ARTS; Film & Video; Reference; Motion pictures; Production and direction; Filmproduktion; Lehrmittel; Filmproduktion; Arbeitstechnik; Einführung; Filmproduktion; Digitale Filmtechnik; Einführung